Risāla-yi Ḥātimiyya - Kāshifī, Wāʿiẓ, (Miras Maktoob, ISBN: 9789004365452., 2019)
Ḥātim al-Ṭāʾī, a pre-Islamic poet from the late sixth century CE, is especially known for his chivalry and magnanimity. A member of the tribe of Ṭayy in Yemen, he is mainly associated with the court of the Lakhmids in Ḥīra in Mesopotamia under king Nuʿmān b. Mundhir (reg. ca. 580-602). His poetry centers around the qualities that earned him his fame, even if part of the poems ascribed to him may be later inventions. Legend has it that his grandfather, who was his guardian, abandoned him when he saw that his grandson's generosity was incurable. Four mourning girls, hewn in stone, lined his grave, together with the cooking pots from which he had served his guests. A popular character in medieval Arabic literature, no separate work was ever dedicated to him, unlike the Persian tradition. The present text on his life and deeds by Wāʿiẓ Kāshifī (d. 910/1504-5) is the oldest to exist in Persian.